Construção de um modelo computacional para simulação do transporte de poluentes em aquíferos - Ghelli, Carolina Angélica (2018)
Due to the considerable increase in the vulnerability of aquifers, the concern is growing mainly by municipalities that relies exclusively on groundwater for their supply. With this, it is necessary to predict the identification of the source of pollution and the movement of the pollutants in the aquifers. Therefore, the objective of this project was to show a computational model with the intention on simulating the transport of pollutants in aquifers. For this, the Finite Differences Method was used for the numerical treatment of the advection-dispersion equation, where the discretization of the advective terms was performed by progressive and regressive differences as a function of the flow velocities and for the diffusive terms the discretization was given by second order central differences. In the treatment of temporal derivatives, the totally implicit scheme was used. For the resolution of the linear system that leads to the calculation of the concentration field, the iterative method of Stabilized and Preconditioned Bi-conjugate Gradients was used. The model was developed in programming language applied to spreadsheets and the results, presented in graph form, were generated in Surfer 10 software. Simulations were applied to single and linear punctuals source. Were performed a simulation of the analytical equation presented by Bear (1979) in order to compare with the results found in the simulations of the developed model and a simulation based on a real area, considering wells of exploitation and injection for remediation of aquifers. The results of the simulations show the evolution of the pollutant plume over time, the concentration values and indicates that the transport of pollutants in aquifers is influenced by the direction of the underground flow.